2009
DOI: 10.1104/pp.109.141291
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Derived Sucrose Is a Key Element in the Symbiotic Association between Trichoderma virens and Maize Plants    

Abstract: Fungal species belonging to the genus Trichoderma colonize the rhizosphere of many plants, resulting in beneficial effects such as increased resistance to pathogens and greater yield and productivity. However, the molecular mechanisms that govern the recognition and association between Trichoderma and their hosts are still largely unknown. In this report, we demonstrate that plant-derived sucrose (Suc) is an important resource provided to Trichoderma cells and is also associated with the control of root coloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
129
1
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(151 citation statements)
references
References 89 publications
(150 reference statements)
15
129
1
6
Order By: Relevance
“…In our study, strain T87 had detrimental effects on tomato roots, and the plants also had a smaller leaf area and a lower true leaf number than the controls in three independent experiments. These results are in disagreement with previous studies indicating that strain T87 (Gv29-8) promoted Arabidopsis seedling growth through production of auxin-like compounds (Contreras-Cornejo et al, 2009) and induced higher photosynthetic rates and systemic increases in the uptake of CO 2 in leaves (Vargas et al, 2009). Interestingly, 18-mer peptaibols from this strain elicited systemic defences against a leaf pathogen in cucumber (Viterbo et al, 2007) and the T87-secreted elicitor Sm1 systematically stimulated defence mechanisms in maize (Djonovic et al, 2007).…”
Section: Resultscontrasting
confidence: 95%
See 1 more Smart Citation
“…In our study, strain T87 had detrimental effects on tomato roots, and the plants also had a smaller leaf area and a lower true leaf number than the controls in three independent experiments. These results are in disagreement with previous studies indicating that strain T87 (Gv29-8) promoted Arabidopsis seedling growth through production of auxin-like compounds (Contreras-Cornejo et al, 2009) and induced higher photosynthetic rates and systemic increases in the uptake of CO 2 in leaves (Vargas et al, 2009). Interestingly, 18-mer peptaibols from this strain elicited systemic defences against a leaf pathogen in cucumber (Viterbo et al, 2007) and the T87-secreted elicitor Sm1 systematically stimulated defence mechanisms in maize (Djonovic et al, 2007).…”
Section: Resultscontrasting
confidence: 95%
“…It has been demonstrated that plant-derived sucrose is an important nutrient source for Trichoderma and is also involved in the control of root colonization (Vargas et al, 2009). However, little is known about the changes influenced by plants in the transcriptome of Trichoderma.…”
Section: Overview Of the Trichoderma Gene Expression Data From Microamentioning
confidence: 99%
“…As indicated above, an auxin-like effect has been observed in etiolated pea stems treated with harzianolide and 6-pentyl-a-pyrone, the major secondary metabolites produced by different Trichoderma strains (Vinale et al, 2008). Maize rhizosphere colonization by T. virens also induces higher photosynthetic rates and systemic increases in the uptake of CO 2 in leaves (Vargas et al, 2009). …”
Section: Plant Growth Promotion and Tolerance To Abiotic Stressmentioning
confidence: 81%
“…Similarly to the situation with mycorrhizae, the highly hydrated polysaccharides of the root-secreted mucigel layer and the mono-and disaccharides excreted by plant roots into the rhizosphere encourage growth of the fungi. It has been observed that plant-derived sucrose is an important resource provided to Trichoderma cells to facilitate root colonization, the coordination of defence mechanisms, and increased rate of leaf photosynthesis (Vargas et al, 2009). Solute transporters such as a di/tripeptide transporter and a permease/intracellular invertase system involved in the acquisition of root exudates have been described in Trichoderma (Vizcaíno et al, 2006;Vargas et al, 2009).…”
Section: Trichoderma Spp Can Colonize Root Intercellular Spacesmentioning
confidence: 99%
“…In this facultative/atypical symbiosis, Trichoderma spp. derive nutrients from the plant host and, in return, provide protection against invading root and foliar pathogens and abiotic stresses (Shoresh et al, 2010;Harman et al, 2004;Vargas et al, 2009Vargas et al, , 2011. The ability of Trichoderma spp.…”
Section: Introductionmentioning
confidence: 99%